1994
DOI: 10.1111/j.1460-9568.1994.tb00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterization of the Shell and Core Territories of the Nucleus Accumbens in the Rat

Abstract: The nucleus accumbens in the rat has been parcelled into shell and core subdivisions. Despite accumulating evidence for such a division of the nucleus accumbens, these territories have not been delineated throughout the rostrocaudal extent of the nucleus. In the present study, an attempt has been made to delineate the shell and core using the distribution of calcium-binding protein immunoreactivity, substance P immunoreactivity and acetylcholinesterase activity in transverse and horizontal sections through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
132
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(146 citation statements)
references
References 35 publications
14
132
0
Order By: Relevance
“…Local intra-NACore antagonism of mAchRs or nAChRs completely and reversibly blocked the acquisition of RMF reinforcement, indicating (1) that activation of both mAchR and nAChR in the NACore is necessary for the conditioning of the positive reinforcing effect of RMF (i.e., for the animal's learning to associate the drug stimulus with the appropriate operant response) and (2) that the ACh release by cholinergic large aspiny interneurons, the second most prevalent neuron population in the striatum including the NACore (Squire et al, 2003), is instrumental for this learning process. Thus, the general rule that striatal cholinergic interneurons play an eminent role in the formation of stimulus-response associations (i.e., learning) (Aosaki et al, 1994;Calabresi et al, 2000;Suzuki et al, 2001;Kitabatake et al, 2003;Mansvelder et al, 2005) also seems to apply to the NACore, a striatal structure dedicated to processing stimuli of high emotional and motivational valence (Haber et al, 1985;Jongen-Relo et al, 1994). Striatal cholinergic interneurons are known to affect GABAergic medium spiny neurons, which constitute the major (95%) neuron population of the striatum and also serve as the major motivational/locomotor output of the striatum (Haber et al, 1985;Heimer et al, 1991;Zahm and Brog, 1992;Meredith and Chang, 1994;Squire et al, 2003;Voorn et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local intra-NACore antagonism of mAchRs or nAChRs completely and reversibly blocked the acquisition of RMF reinforcement, indicating (1) that activation of both mAchR and nAChR in the NACore is necessary for the conditioning of the positive reinforcing effect of RMF (i.e., for the animal's learning to associate the drug stimulus with the appropriate operant response) and (2) that the ACh release by cholinergic large aspiny interneurons, the second most prevalent neuron population in the striatum including the NACore (Squire et al, 2003), is instrumental for this learning process. Thus, the general rule that striatal cholinergic interneurons play an eminent role in the formation of stimulus-response associations (i.e., learning) (Aosaki et al, 1994;Calabresi et al, 2000;Suzuki et al, 2001;Kitabatake et al, 2003;Mansvelder et al, 2005) also seems to apply to the NACore, a striatal structure dedicated to processing stimuli of high emotional and motivational valence (Haber et al, 1985;Jongen-Relo et al, 1994). Striatal cholinergic interneurons are known to affect GABAergic medium spiny neurons, which constitute the major (95%) neuron population of the striatum and also serve as the major motivational/locomotor output of the striatum (Haber et al, 1985;Heimer et al, 1991;Zahm and Brog, 1992;Meredith and Chang, 1994;Squire et al, 2003;Voorn et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the NAC consists, in fact, of two neuroanatomically and neurochemically distinct regions, a "core" (NACore) and a "shell" (NAShell) (Heimer et al, 1991;Jongen-Relo et al, 1994;Haber et al, 1995). Converging evidence from a number of laboratories suggests that the evaluation of (1) the interoceptive ("direct pharmacological") stimulus of the drug of abuse itself (Pontieri et al, 1995) and of (2) drug-associated stimuli (discriminative stimuli as well as secondary reinforcing stimuli) (Ito et al, 2000;Ciccocioppo et al, 2001;Ghitza et al, 2003) is performed in the NAShell, whereas the learned ("conditioned") response to such stimuli (i.e., drug seeking) is executed by the NACore (Shippenberg et al, 1992;Ito et al, 2000;Neisewander et al, 2000;Phillips et al, 2003;Koob et al, 2004;Peoples et al, 2004;Voorn et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunctions of this region may be involved in conditions such as schizophrenia, drug addiction and other neuropsychiatric disorders (Koob and Bloom 1988;O'Donnell and Grace 1998). The NAc has two major subregions-the shell and the core-defined by histochemical, electrophysiological, connectivity and cellular criteria (O'Donnell and Grace 1993;Jongen-Relo et al 1994). This structure receives glutamatergic projections from the ventral hippocampus (vHC) (DeFrance et al 1985), which is involved in generating context, task attention and emotion (Fanselow and Dong 2010); the basolateral nucleus of the amygdala (BLA) (Groenewegen et al 1980;McDonald 1991), which mediates emotional behaviour; and the prefrontal cortex (Fuller et al 1987), which modulates activity throughout the limbic system to enable behavioural flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has become evident that the nucleus accumbens is a heterogeneous structure. At least two different parts can be discerned: the shell and the core (Voorn et al 1986;Groenewegen et al 1987;Heimer et al 1991;Zahm and Brog 1992;Brog et al ted from the shell was significantly attenuated by prior 1993; Meredith et a l 1993;Jongen-Relo et al 1994). administration of either the dopamine D?…”
Section: Introductionmentioning
confidence: 99%